Absence of association between gallstone and coronary artery calcification. (March 2017) - Kwon, Chang Hee; Kang, Jung Gyu; Lee, Hyun Jong; Kim, Nan Hee; Sung, Joo-Wook; Cheong, EunSun; Sung, Ki-Chul
Abstract: Background and aims: Gallstone has been suggested to be associated with cardiovascular disease (CVD). Coronary artery calcification (CAC) is an excellent value to predict future CVD. The aim of this study was to evaluate the association between gallstone and CAC. Methods: Data were analyzed from an occupational cohort of 46, 893 subjects (37, 557 men and 9336 women) between 2011 and 2014. Participants with cancer or CVD histories or missing data at baseline were excluded from the study. Gallstone was diagnosed by ultrasound-documentation. Multivariate logistic analysis was conducted to examine the relationship between gallstone and CAC. Results: The total population who had gallstone was 1426 (3.1%). In multivariate analysis, odds ratios (OR) for gallstone were not different according to CAC score groups in men and women. In addition, gallstone was not associated with higher OR for CAC in men and women. Conclusions: Gallstone was not associated with CAC in both Korean men and women. Highlights: Gallstone was associated with traditional cardiovascular risk factors. Gallstone was not associated with coronary artery calcification as a significant predictor of cardiovascular disease (CVD). Our findings imply that gallstone and CVD may be epiphenomenon.